NGAYAH: TRANSFORMASI NILAI SOSIAL - Ni Nyoman Wati (Pascasarjana Institut Seni Indonesia Surakarta, 2008)
This paper describes a performance entitled ngayah, that is an important activities in Balinese society. The activities which do not aimed to gain material advantages is assumed consist of high value in society. Based on experience through her whole life and research held on three cases, the writer transformed those social activities to the performing art. The performance means to aware and actualize the value of ngayah in contemporary era. Key words: ngayah, social activities, value, performance.